Utilization of the Django Framework as a Dashboard Model Information System for Raw Material Inventory on PT Bimasakti Karyaprima - Alfeno, Sandro; Rifai, Danang; saepudin, muhammad (Pandawan, 2019)
The aim of the research is to analyze the raw material inventory and design a dashboard system that can help achieve company goals. The research method used is the method of analysis of stash, software design methods, and methods of software testing. The design analysis method used is the SWOT analysis, the design method used is the design concept using UML diagrams, the soft test method uses the Black Box concept. The results achieved are a dashboard system used by the Warehouse Section and Production Section to monitor raw material inventories and production performance. The conclusion of this study is that the dashboard application that has been made can help the Warehouse and Production Section to monitor raw material inventory and production performance in real time. This web application provides information easily, quickly, concisely and interactively which includes raw materials for shoe components, office equipment, production tools and general equipment, inventory planning, recommendations and reports on transactions and raw material requests. Keywords : Dashboard, Material